Refined weld microstructure and enhanced joint mechanical property of 1460 Al-Li alloys via double-pulsed variable polarity TIG arc welding. (October 2022) - Sun, Xuejun; Qi, Bojin; Jiang, Zihao; Zeng, Caiyou; Cong, Baoqiang
Abstract: In this work, 1460 Al-Li alloy plates (thickness 2 mm) were butt-welded by using conventional variable polarity TIG welding (VPTIG), low-frequency pulsed (2 Hz) variable polarity TIG welding (P-VPTIG), and double-frequency (low-frequency (2 Hz) + ultrasonic-frequency (20 kHz)) pulsed variable polarity TIG welding (DP-VPTIG). The influences of the three current modes on the weld microstructure and mechanical properties were investigated contrastively. Weld microstructure was characterized by a metallographic optical microscope, scanning electron microscope, and electron backscattering diffraction technology. The mechanical properties of those 1460 Al-Li alloy-based joints were measured by microhardness and room-temperature uniaxial tensile test. Obtained results indicated that modulating pulsed current on the conventional VPTIG current can effectively eliminate the coarse columnar structures, resulting in whole refined equiaxed grains in the weld zone (WZ) and fusion zone (FZ). By comparison, DP-VPTIG current exhibited the most prominent effect of homogenization and refinement on the weld microstructure. In addition, it significantly increased the quantity and width of the fine strip-like equiaxed grain zone. The eutectic phase particles distributed in the grain boundaries were refined prominently by the modulation of pulsed current. Compared with the VPTIG process, both P-VPTIG and DP-VPTIG processes effectively enhanced the strength and elongation of 1460 Al-Li alloy-based joints, with an increase of 6.2 % and 10.9 % in tensile strength and 16 % and 128.6 % improvement in elongation, respectively.